On distribution of values of multiplicative functions - Grigelionis, B. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис. О распределении значений мультипликативных функцийB. Grigelionis. Apie multiplikatyvinių funkcijų reikšmių pasiskirstymą